Discovering Spirituality: A Guide for Teens - Larry Forthun; Angelica Johns (EDIS, 2011)
Who am I? What is my purpose? Have you ever asked yourself these questions? You’re not alone. Every teenager at one time or another has asked these questions. It’s the answers that are hard to figure out. Searching for a sense of meaning and purpose in life is not easy. However, you can do a few things that will help you discover the answers. One of the most important is discovering your spirituality. This 2-page fact sheet was written by Larry Forthun and Angelica Johns and published by the UF Department of Family Youth and Community Sciences, May 2011.